SUSCETIBILIDADE DE NOCTUÍDEOS DE IMPORTÂNCIA AGRÍCOLA A FLUBENDIAMIDA, CLORANTRANILIPROLE E INDOXACARBE - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
Noctuids stand out among the main groups of Lepidoptera that cause damage to crops. They exhibit great diversity of species of high economic important pests. Among them, we can highlight the occurrence of Soybean Looper, Chrysodeixis includens (Walker), species from the genus Spodoptera such as S. cosmioides (Walker), S. eridania (Cramer) and S. frugiperda (Walker) and even species of the subfamily Heliothinae, such as Helicoverpa armigera (Hübner). The search for alternatives to control these species has enabled the introduction of more environmentally safe insecticides and high insecticidal activity, such as the group of diamides and oxadiazines. Our objective was quantify the susceptibility of C. includens, H. armigera, S. frugiperda, S. cosmioides and S. eridania to flubendiamide, chlorantraniliprole and indoxacarb, through bioassays with application of insecticide incorporated in the artificial diet. Samples were collected during the seasons 2013/2014 and 2014/2015, in different regions of Brazil. Bioassays were developed at the Entomology Laboratory of Embrapa-Soja in Londrina. The mortality evaluation and weighing of caterpillars survivors were held on the seventh day. Mortality data were subjected to Probit’s analysis to estimate LC50 and LC99. Larval weight data were subjected to analysis of variance and means compared by Skott-Knott test at 5% probability. The LC50 of the C. includens population ranged from 0.861 to 187.28 μg of a.i./mL of diet (flubendiamide), 0.025 to 5.331 (chlotantraniliprole) and 1.345 to 2.94 (indoxacarb). For H. armigera ranged from 0.076 to 0.093 (flubendiamide), 0.050 to 0.051 (chlorantraniliprole) and 1.581 (indoxacarb). The LC50 for S. frugiperda, S. cosmioides and S. eridania ranged from 0.255 to 2.73 (flubendiamide), 0.032 to 0.104 (chlorantraniliprole), 0.834 to 3.0886 (indoxacarbe). Discriminating concentrations suggested for monitoring resistance of C. includens were 12 and 120 μg of flubendiamide/ml of diet, 9 and 90 μg of chlorantraniliprole/ml of diet and 5 and 50 μg of indoxacarb/ml of diet. The high variations found in susceptibility to diamides in populations of C. includens indicate resistance of Montividiu-GO and Campo Verde-MT populations. Among the insecticides studied, chlorantraniliprole have greater potential for controlling H. armigera, S. frugiperda, S. eridania and S. cosmioides.
Keywords: bioensaio; diamidas e oxadiazinas; bioassay; diamides and oxadiazines; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA